New perspectives on bare noun phrases in romance and beyond - Kabatek, Johannes; Wall, Albert (Linguist) (Studies in language companion series, 2013)
This paper investigates distributional and semantic properties of two kinds of indefinite NPs in Bulgarian: bare nouns vs. NPs headed by edin 'one'. The central question, which constitutes a subject of intense debate in the literature, is whether there is a semantic (and pragmatic) difference between these two kinds of indefinites. It will be argued in favour of such a distinction. This claim is supported by different properties which these two kinds of Bulgarian indefinites display concerning their scope behaviour in opaque contexts, the choice of discourse anaphora, the use of wh-words, and.